Pengaruh Biaya Lingkungan, Kinerja Lingkungan, dan Kepemilikan Asing Terhadap Kinerja Keuangan Perusahaan - Wicaksono, Crescentiano Agung (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The food industry is not only responsible for providing food resources but also has significant impacts on the environments. This article discusses the challenges faced by companies in the food subsector in balancing global food needs and environmental sustainability. This research uses a research method with purposive sampling technique to identify samples for companies in the food and beverages sub-sector. The number of food and beverage sub-sector companies registered on the IDX for the 2016-2021 period is 29 companies, and 7 companies that meet the research criteria. The analysis results show that environmental performance does not affect financial performance, while environmental costs and share ownership negatively affect financial performance. Simultaneously, environmental performance, environmental costs, and share ownership affect financial performance. The research results can be a reference for companies in general dan food and beverage sub-sector companies in particular in making decisions related to environmental aspects in an effort to increase financial profits for the company.